Additional diagnostic value of ratio indices of quantitative contrast-enhanced ultrasound parameters in small solid C-TIRADS 4 thyroid nodules - Xie, Jiayi; Liu, Wengang; Zhou, Jinguang; Zhou, Ping (Frontiers in Oncology, 2025)
BackgroundTo investigate the efficacy of contrast-enhanced ultrasound (CEUS) parameters, particularly ratio indices of quantitative CEUS parameters, for differentiation of small solid C-TIRADS 4 thyroid nodules.Materials and methods235 small solid C-TIRADS 4 thyroid nodules with determinate pathological results, including 175 nodules in the training cohort and 60 nodules in the validation cohort were retrospectively evaluated. The ratio indices of the internal tissue to peripheral tissue and the internal tissue to healthy tissue of quantitative parameters were calculated. In the training cohort, the meaningful quantitative ratio indices with an AUC > 0.7 and qualitative parameters were further included in multivariate regression analysis. The diagnostic efficacy of the logistic model was evaluated.ResultsIn single-factor analysis, C-TIRADS, enhancement degree, mTTI ratio (L/P), TTP ratio (L/P), WiR ratio (L/P), WoR ratio (L/P) and TTP ratio (L/H) were significant parameters for differentiation of thyroid nodules (P < 0.05). The multifactor analysis showed that there was significant difference in C-TIRADS, mTTI ratio (L/P), TTP ratio (L/P), WiR ratio (L/P), WoR ratio (L/P) and TTP ratio (L/H) between two groups (P < 0.05). The logistic model was generated, and the AUC, sensitivity, specificity, and accuracy of the training cohort were 0.935(95% CI: 0.888–0.967),85.71%, 88.57%, and 86.86%, respectively. The logistic model demonstrated significantly higher diagnostic performance compared to individual parameters (P < 0.001). In the validation cohort, the diagnostic model had an AUC of 0.910,sensitivity of 87.9%, specificity of 92.6%, and accuracy of 90.25%.ConclusionRatio indices of quantitative parameters have high diagnostic values in differentiating small solid thyroid nodules. Combining C-TIRADS with both qualitative and quantitative CEUS parameters enhances the diagnostic accuracy of malignant thyroid nodules.